Sequential CD19 and BCMA‐specific CAR T‐cell treatment elicits sustained remission of relapsed and/or refractory myeloma. (23rd December 2020) - Yan, Lingzhi; Qu, Su; Shang, Jingjing; Shi, Xiaolan; Kang, Liqing; Xu, Nan; Zhu, Mingqing; Zhou, Jin; Jin, Song; Yao, Weiqin; Yao, Ying; Chen, Guanghua; et al.
Abstract: The low rate of durable response against relapsed and/or refractory multiple myeloma (RRMM) in recent studies indicates that chimeric antigen receptor T‐cell (CART) treatment is yet to be optimized. This study aims to investigate the safety and efficacy of sequential infusion of CD19‐CART and B‐cell maturation antigen (BCMA)‐CARTs for RRMM with a similar 3 + 3 dose escalation combined with a toxicity sentinel design. We enrolled 10 patients, among whom 7 received autologous infusion and 3 received allogeneic infusion. The median follow‐up time was 20 months. The most common grade 3/4 treatment‐emergent toxicities were hematological toxicities. Cytokine‐release syndrome (CRS) adverse reactions were grade 1/2 in 9 out of 10 subjects. No dose‐limited toxicity (DLT) was observed for BCMA‐CAR‐positive T cells ≤5 × 10 7 /kg), while two patients with dose‐levels of 5–6.5 × 10 7 /kg experienced DLTs. The overall response rate was 90% (five partial responses and four stringent complete responses). Three out of four patients with stringent complete responses to autologous CART had progression‐free survival for over 2 years. The three patients with allogeneic CART experienced disease progression within 2 months. These results evidence the sequential infusion's preliminarily tolerability and efficacy in RRMM, and present a simple and safe design applicable for the establishment of multiple CART therapy. Abstract : We conducted a pilot study to assess the feasibility of the sequential infusion of CD19 and B‐cell maturation antigen (BCMA)‐specific chimeric antigen receptor T‐cell (CART) for relapsed and/or refractory multiple myeloma treatment with a similar 3 + 3 dose escalation design. Translational Significance: The favorable and persistent responses against RRMM were observed in those patients with a combined infusion of autologous CD19‐CART and BCMA‐CART. The emergence of intolerant adverse event (neurotoxicity and sever CRS) was associated with increased dose level of BCMA‐CARTs infusion.